167k views
2 votes
Solve this quadratic function algebraically

Please expalin how you got your answer

F(X)= 3x2-6

User Gajotres
by
6.3k points

1 Answer

5 votes

Answer:

Explanation:

Please use " ^ " to denote exponentiation: f(x)= 3x^2 - 6.

f(x)= 3x^2 - 6 can be factored (not solved) as follows:

f(x)= 3(x^ 2 -1) = 3(x - 1)(x + 1).

If you want a "solution," you must set f(x)= 3(x^ 2 -1) = 3(x - 1)(x + 1) = to 0 and solve the resulting equation for x: x = 1 and x = -1.

User XING
by
6.5k points